Outstanding treatment success of pembrolizumab and bevacizumab combination therapy in first-line treatment of cervical sarcomatoid carcinoma: a rare case report - Zhang, Mingzi; Li, Xinbei; Huang, Zhonghua; Yang, Zhenjiang; Yang, Lina (Frontiers in Oncology, 2025)
BackgroundCervical lesions of sarcomatoid carcinoma are very rare, and there are still no reports of any targeted drugs applied in this rare tumor. In this report, we document a patient with stage IVA sarcomatoid carcinoma of the cervix, according to the FIGO staging system. The genetic testing of the patient’s tumor tissue indicated the expression of PD-L1. This finding is significant as it suggests that the patient may be a candidate for immunotherapy. In this manuscript, we report a case of a patient who achieved a transient recurrence-free survival period through combined therapy (although recurrence eventually occurred), with a progression-free survival exceeding 13 months and an overall survival exceeding 22 months (as of the last follow-up, the patient was receiving palliative care only).Case presentationAfter diagnostic confirmation, the patient was administered a first-line combination therapy consisting of pembrolizumab plus bevacizumab. After 2 cycles of treatment, there was a marked reduction in tumor volume and the patient did not experience any side effects. Since then, the patient has continued to receive the regimen and the tumor has continued to shrink. Ultimately, after 10 courses of treatment with immune checkpoint inhibitors and anti-angiogenic drugs, the PET-CT scan showed complete disappearance of the tumor, with no evidence of cancer throughout the body. Subsequently, the patient continued to receive maintenance therapy with the same regimen, with regular follow-up evaluations. No recurrence was detected until 13 months later, when a MRI scan revealed tumor recurrence.ConclusionsThe combination of a PD-1 inhibitor with a drug that promotes tumor vascular normalization has shown promise in treating advanced cervical sarcomatoid carcinoma. We are the first to report the use of this combination regimen in this rare tumor, where previously reported treatment has been with chemotherapy agents. In addition, the level of PD-L1 expression could serve as a potential biomarker to predict the response to immunotherapy in patients with advanced sarcomatoid carcinoma of the cervix. Our case highlights the efficacy of immunotherapy in combination with anti-angiogenic targeted therapy for the treatment of sarcomatoid carcinoma of the cervix.